2010
DOI: 10.1007/s10295-010-0783-9
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of a continuous culture of Saccharomyces cerevisiae with the yeast Issatchenkia orientalis in the production of ethanol at increasing temperatures

Abstract: A fermentation system was continuously fed with sugar-cane syrup and operated with recycling of Saccharomyces cerevisiae cells at temperatures varying from 30 to 47 °C. The aim of the present work was to obtain and study the colonies of isolates showing elongated cells of yeasts which were sporadically observed at the end of this continuous process. Based on a sequence of assays involving methods of classical taxonomy and RAPD-PCR, two groups of isolates showing characteristics of non-Saccharomyces yeasts were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…Although the mechanism behind formation of pseudohyphae or their role in cell metabolism is not clear, it is thought that the pseudohyphae are formed during depletion of nutrients, especially the nitrogen source. Most of the morphological and physiological characteristics and the ability of the yeast cells used in the present study to assimilate specific sugars and nitrogen sources resembled the characteristics shown by the group-I non-Saccharomyces isolates belonging to I. orientalis reported previously [11]. They also identified a gene FLO11 that encodes a cell wall protein, which is critically required for both invasion and pseudohyphae formation in response to nitrogen starvation.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Although the mechanism behind formation of pseudohyphae or their role in cell metabolism is not clear, it is thought that the pseudohyphae are formed during depletion of nutrients, especially the nitrogen source. Most of the morphological and physiological characteristics and the ability of the yeast cells used in the present study to assimilate specific sugars and nitrogen sources resembled the characteristics shown by the group-I non-Saccharomyces isolates belonging to I. orientalis reported previously [11]. They also identified a gene FLO11 that encodes a cell wall protein, which is critically required for both invasion and pseudohyphae formation in response to nitrogen starvation.…”
Section: Discussionsupporting
confidence: 80%
“…Gallardo et al [11] observed the pseudohyphae formation for non-Saccharomyces isolates after 3 days of growth. Although the mechanism behind formation of pseudohyphae or their role in cell metabolism is not clear, it is thought that the pseudohyphae are formed during depletion of nutrients, especially the nitrogen source.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that strains K1 and C1 produced sufficient ethanol at levels to be somewhat inhibitory and thus cause a decrease in biomass synthesis compared to previous studies. Gallardo et al [38] and Shin et al [39] detected ethanol during I. orientalis fermentation. Some yeast species produce ethanol even in aerobic cultures at sugar concentrations of more than approximately 0.04 g L −1 glucose.…”
Section: Methionine Content In Yeastsmentioning
confidence: 99%
“…[19,22,[38][39][40] Yeast biomass in this study was between 0.12 and 1.33 g L −1 (0.0001 to 0.0013%). It is possible that strains K1 and C1 produced sufficient ethanol at levels to be somewhat inhibitory and thus cause a decrease in biomass synthesis compared to previous studies.…”
Section: Methionine Content In Yeastsmentioning
confidence: 99%
“…The precultured P. kudriavzevii or S. cerevisiae was cultivated in YEPD liquid medium under various environmental stresses: high NaCl concentrations (10,20,40 and 60 g/L), low pH (pH 4, 3, 2 and 1), high Cu concentrations (0.5, 1, 3 and 4 mmol/L), high Zn concentrations (0.5, 1, 3 and 4 mmol/L) and high Cd concentrations (0.05, 0.1, 0.2 and 0.5 mmol/L). The initial biomass concentration was 0.1 g dry weight/L.…”
Section: Tolerance To Various Environmental Stressesmentioning
confidence: 99%